2020
DOI: 10.1039/c9mh00969h
|View full text |Cite
|
Sign up to set email alerts
|

A highly asymmetric interfacial superstructure in WC: expanding the classic grain boundary segregation and new complexion theories

Abstract: The discovery of a grain boundary superstructure with highly asymmetric and off-the-center segregation, along with interfacial disordering and symmetry change on the opposite sides, extends our knowledge of grain boundary segregation and complexions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…This series of For Li-M systems, however, the interfacial coefficient f(h) should be more complex than the overly simplified "hard spheres" model due to strong Li-M bonding, so we do not expect a simple series of Dillon-Harmer complexions to occur in a sequence. Here, reconstruction like those observed in the Ni-Bi 65,66 , Cu-Bi 76 , Al-Cu 77 , Si-Au 73,78 , or transition metal doped WC 79 are expected (with possibly even more complexity and diversity). Disordered interfacial phases (nanoscale amorphous-like intergranular films) similar to those observed in W-Ni 80,81 , Mo-Ni 82 ,…”
Section: Thermodynamically-controlled Interfacial Engineering: a New supporting
confidence: 62%
“…This series of For Li-M systems, however, the interfacial coefficient f(h) should be more complex than the overly simplified "hard spheres" model due to strong Li-M bonding, so we do not expect a simple series of Dillon-Harmer complexions to occur in a sequence. Here, reconstruction like those observed in the Ni-Bi 65,66 , Cu-Bi 76 , Al-Cu 77 , Si-Au 73,78 , or transition metal doped WC 79 are expected (with possibly even more complexity and diversity). Disordered interfacial phases (nanoscale amorphous-like intergranular films) similar to those observed in W-Ni 80,81 , Mo-Ni 82 ,…”
Section: Thermodynamically-controlled Interfacial Engineering: a New supporting
confidence: 62%
“…Moreover, the L0 layer provides a similar octahedral coordination compared with that of TiC, while the L layer offers a distorted octahedral coordination. It helps to explain the preferential segregation of Ti in the L0 layer (versus the L layer) from the consideration of coordination environments ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Kohn-Sham equations were solved by using the projected-augmented wave method ( 47 , 48 ). The nonlocal optB86b-vdW functional was selected for structural optimization of WC interfacial structures based on prior work ( 17 ). Because of the large crystal structure, the Brillouin zone integrations were sampled on a Γ-centered 1 × 1 × 1 grid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al found a temperature dependent segregation behavior including a first order congruent transition at low temperatures in a planar Au-doped Si GB using atomistic calculations [14]. Very recently, a complex co-segregation pattern including segregation induced symmetry changes and order losses at a planar WC grain boundary was discovered [15]. A comprehensive review on evidence of grain boundary transitions can be found in a recent review article [16].…”
mentioning
confidence: 99%